CD122-targeted interleukin-2 and αPD-L1 treat bladder cancer and melanoma via distinct mechanisms, including CD122-driven natural killer cell maturation - Ryan M Reyes (Taylor & Francis Group, 2021)
Bladder cancer (BC) and melanoma are amenable to immune checkpoint blockade (ICB) therapy, yet most patients with advanced/metastatic disease do not respond. CD122-targeted interleukin (IL)-2 can improve ICB efficacy, but mechanisms are unclear. We tested αPD-L1 and CD122-directed immunotherapy with IL-2/αIL-2 complexes (IL-2c) in primary and metastatic bladder and melanoma tumors. IL-2c treatment of orthotopic MB49 and MBT-2 BC generated NK cell antitumor immunity through enhanced activation, reduced exhaustion, and promotion of a mature, effector NK cell phenotype. By comparison, subcutaneous B16-F10 melanoma, which is IL-2c sensitive, requires CD8+ T and not NK cells, yet we found αPD-L1 efficacy requires both CD8+ T and NK cells. We then explored αPD-L1 and IL-2c mechanisms at distinct metastatic sites and found intraperitoneal B16-F10 metastases were sensitive to αPD-L1 and IL-2c, with IL-2c but not αPD-L1, increasing CD122+ mature NK cell function, confirming conserved IL-2c effects in distinct cancer types and anatomic compartments. αPD-L1 failed to control tumor growth and prolong survival in B16-F10 lung metastases, yet IL-2c treated B16-F10 lung metastases effectively even in T cell and adaptive immunity deficient mice, which was abrogated by NK cell depletion in wild-type mice. Flow cytometric analyses of NK cells in B16-F10 lung metastases suggest that IL-2c directly boosts NK cell activation and effector function. Thus, αPD-L1 and IL-2c mediate nonredundant, immune microenvironment-specific treatment mechanisms involving CD8+ T and NK cells in primary and metastatic BC and melanoma. Mechanistic differences suggest effective treatment combinations including in other tumors or sites, warranting further studies.